UJI BIOAKTIVITAS EKSTRAK DAUN BIDARA BIDARA (ZIZIPHUS MAURITIANA LAM) TERHADAP PERTUMBUHAN STAPHYLOCOCCUS AUREUS - Aan Yulianingsih; Dzikra Arwie (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2019)
The background of this study is Staphylococcus aureus is an anaerobic facultative bacterium and one of the normal microflora in the mouth. However, if it is influenced by predisposing factors, it will become a pathogen. Bidara leaves have antimicrobial activity against Staphylococcus aureus, because Bidara leaves contain various compounds including alkaloids, flavonoids, steroids, tannins and essential oils. The purpose of this study was to determine how much inhibitory power produced by Bidara leaf extract on the growth of Staphylococcus aureus bacteria. This research method is a laboratory experimental research using the diffusion test (wells) method. The sample of this study was Staphylococcus aureus. Dilution of Bidara leaf extract consists of 5 concentrations including: 20%, 40%, 60%, 80%, and 100%. Chlorampheniocol is used for Positive control while Negative control uses aquadest. Based on observations show that the average diameter of inhibitory zone Bidara leaf extract at a concentration of 20% with a diameter of 10.5 mm (R), at a concentration of 60% and 80% with a diameter of 16 mm and 18 mm (I), at a concentration of 100% with a diameter of 24 mm (S). It can be concluded that the higher the concentration of Bidara leaf extract, the inhibition zone formed will increase. So Bidara leaves are good for use in treating infections caused by Staphylococcus aureus bacteria.